A simple education tool for ventricular assist device patients and their caregivers - Barber, J.; Leslie, Gavin (2015)
Background: Ventricular assist devices (VADs) have become an important therapy in the management of patients with end-stage heart failure. Driveline infection is the most common late-onset complication in this group of patients. Patients and their caregivers require education regarding management of the driveline to reduce the risk of infection when they are discharged home with a VAD. Purpose: The aim of this study was to develop an educational booklet on VAD driveline care for patients and their caregivers. A literature review was undertaken to explore the availability of patient education material pertaining to driveline management and to update evidence-informed knowledge that could potentially reduce infection rates in these patients. This information was evaluated by peers, patients, and caregivers to produce the final colored booklet. Conclusions: Driveline care is not comprehensively discussed in the literature and lacks detail in the particulars of wound care, patient education, and the adaptation of driveline care to the patient's home environment. An educational booklet was designed to convey what is currently known about preventing driveline infections to those who are responsible for providing the required daily care. Evaluation of patient education material by those using the material is essential. As with all written material, the information will require updating as new evidence becomes available.Clinical Implications: Managing driveline infection risk for patients at home with extended therapy is a critical nursing issue in improving morbidity and mortality. After VAD implantation, patients and caregivers must be educated about the ongoing care of the driveline exit site to minimize the risk of infection. A rigorously developed and patient-evaluated educational booklet on driveline exit site care can be a valuable reference tool for patients and caregivers after hospital discharge.